2022
DOI: 10.1093/ajcn/nqac028
|View full text |Cite
|
Sign up to set email alerts
|

Changes in anemia and anthropometry during adolescence predict learning outcomes: findings from a 3-year longitudinal study in India

Abstract: Background Anemia and poor physical growth during adolescence have far-ranging consequences, but limited longitudinal evidence exists on how changes in these factors relate to changes in learning skills as adolescents mature. Objectives We examined the association between changes in anemia and physical growth during adolescence and learning outcomes. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 57 publications
0
8
1
Order By: Relevance
“…Based on 9 studies from 5 countries, this analysis demonstrated that increasing iron supplementation dosage could improve intelligence test scores, but had no efect on attention, short-term memory, long-term memory, or academic performance. Moreover, there were two large-scale observational studies, one crosssectional and one longitudinal, which supported an association between anemia and academic performance in adolescents [11,12].…”
Section: Introductionmentioning
confidence: 78%
“…Based on 9 studies from 5 countries, this analysis demonstrated that increasing iron supplementation dosage could improve intelligence test scores, but had no efect on attention, short-term memory, long-term memory, or academic performance. Moreover, there were two large-scale observational studies, one crosssectional and one longitudinal, which supported an association between anemia and academic performance in adolescents [11,12].…”
Section: Introductionmentioning
confidence: 78%
“…So it is important that future studies on balanced nutritional intake and standardized Fe supplementation for stunting prevention in adolescence are important. (6). Stunting cannot be separated from nutritional status, there are three main things that affect nutritional status including food safety (quantity and quality of food) which is an important factor for stunting, inadequate care, and health (disease infection) (7).…”
Section: Discussionmentioning
confidence: 99%
“…Anemia in pregnancy can be a predictor of stunting events (11). Anemia in adolescent girls will also affect physical activity, learning concentration which will affect adolescent girls achievement (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In adolescents, anaemia is associated with compromised growth (7) , decreased cognitive function and depressed immune function (8,9) . A recent study in India reported that persistent anaemia in adolescents was associated with poor learning outcomes (10) . In adulthood, anaemia can impact productivity and overall quality of life (11) .…”
mentioning
confidence: 99%